Unprecedented irradiation resistance of nanocrystalline tungsten with equiaxed nanocrystalline grains to dislocation loop accumulation. (15th February 2019) - El-Atwani, O.; Esquivel, E.; Aydogan, E.; Martinez, E.; Baldwin, J.K.; Li, M.; Uberuaga, B.P.; Maloy, S.A.
Abstract: Nanocrystalline metals are often postulated as irradiation tolerant materials due to higher grain boundary densities. The efficiency of these materials in mitigating irradiation damage is still under investigation. Here, we present an in-situ transmission electron microscopy with ion irradiation study on equiaxed 35 nm grained tungsten (NCW-35 nm) and compare its radiation tolerance, in terms of dislocation loop damage, to several other grades of tungsten with different grain sizes at two temperatures (RT and 1073 K). The NCW-35 nm was shown to possess significant higher radiation tolerance in terms of loop damage. As demonstrated by Kinetic Monte Carlo simulations, at least part of the higher radiation tolerance of the small grains is due to higher interstitial storage (at the grain boundaries) and defect recombination (in the grain interiors) in the small grain material. In addition, experimental observations reveal rapid and efficient dislocation loop absorption by the grain boundaries and this is considered the dominant factor for mass transport to the boundaries during irradiation, enabling the remarkable radiation tolerance of 35 nm grained tungsten. This study demonstrates the possibility of attaining high radiation tolerant materials, in terms of dislocation loop damage, by minimizing grain sizes in the nanocrystalline regime. Graphical abstract: The response of different tungsten material grades to 1 MeV Kr +2 heavy ion irradiation at different conditions. Image 1